National Health Insurance. Memorandum on certification of incapacity for work. giving the results of recent investigations as to the causes of increase of claims to sickness and disablement benifit (Wyman, 1931)
This memorandum is issued on behalf of the Ministry of Health for England and Wales, the department of Health for Scotland and the National Health Insurance Joint Committee.